2011
DOI: 10.1002/ijc.26183
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin increases B‐cell‐lymphoma‐2 expression via activation of protein kinase C and Akt2 in endometrial cancer cells

Abstract: Human carcinomas often show resistance to cisplatin and Bcl‐2 is associated with resistance to cisplatin. However, Bcl‐2 regulation on cisplatin treatment in human cancers is unknown. Here, we show a novel mechanism by which cisplatin treatment promotes resistance by increasing the expression of Bcl‐2 mRNA. Bcl‐2 mRNA and protein expression was increased in cisplatin‐resistant endometrial cancer cell lines (KLE and HEC‐1‐A), but not in cisplatin‐sensitive cell line (Ishikawa). Cisplatin‐mediated increase in Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…19 An increase in the expression of Bcl-2 mRNA and protein is associated with resistance to CDDP in CDDP-resistant endometrial cancer cell lines, but not in CDDP-sensitive cell lines. 20 Our results show that in the CDDP-resistant A2780cis cells, CDDP did not downregulate Bcl-2 but Nut3a and CDDP plus Nut3a did. Finally, CDDP alone does not decrease Bcl-2 levels, but in combination with metformin, Bcl-2 is downregulated in OVCa cells.…”
Section: Cancer Cell Biologymentioning
confidence: 42%
“…19 An increase in the expression of Bcl-2 mRNA and protein is associated with resistance to CDDP in CDDP-resistant endometrial cancer cell lines, but not in CDDP-sensitive cell lines. 20 Our results show that in the CDDP-resistant A2780cis cells, CDDP did not downregulate Bcl-2 but Nut3a and CDDP plus Nut3a did. Finally, CDDP alone does not decrease Bcl-2 levels, but in combination with metformin, Bcl-2 is downregulated in OVCa cells.…”
Section: Cancer Cell Biologymentioning
confidence: 42%
“…Activation of the PI3K/AKT/mTOR pathway has also been implicated as a mechanism of resistance to standard cytotoxic agents in endometrial cancer (76,77), and combining these agents with PI3K/AKT/mTOR pathway inhibitors has resulted in improved efficacy in numerous model systems (44), including endometrial cancer models (78). In a phase I trial of temsirolimus in combination with carboplatin and paclitaxel in advanced solid tumors, 9 of 11 patients (82%) with endometrial cancer achieved objective partial responses (79).…”
Section: Combining Pi3k/akt/mtor Inhibition With Other Therapiesmentioning
confidence: 43%
“…Studies using chemoresistant cell lines and RNAi have been conducted to assess the effect of individual AKT isoforms on drug resistance. Results have shown that while all three isoforms were necessary for optimal cell proliferation, apoptosis evasion, and cell survival, AKT2 was most crucial in chemoresistance (Girouard et al 2013); this is in accordance with previous studies which suggested that elevated AKT2 activation following cisplatin treatment was responsible for Bcl2 activation and reduced apoptosis (Rouette et al 2012). Finally, we have previously shown that AKT regulates PTGS2 expression in EC through the activation of the NFkB pathway; this, in turn, enables enhanced angiogenesis, tumor invasiveness, and potentially chemoresistance (St-Germain et al 2004a,b, Chaudhry & Asselin 2009).…”
Section: R91mentioning
confidence: 44%